Clima organizacional en la cooperativa de ahorro y crédito Occidental periodo 2022 – 2023 - Jiménez Mullo, Donovan Adrián (2023)
The organizational climate promotes within organizations a good relationship between the institution and collaborators, and infers motivation, satisfaction and performance at work. A good organizational climate can promote cohesion and teamwork, while a bad organizational climate can lead to decreased productivity. This research project called "Organizational climate in the Western Savings and Credit Cooperative Period 2022 - 2023", aims to promote strategies to improve the organizational climate in the cooperative. Under a theoretical support based on books and academic articles and with the application of a research methodology based on a quantitative approach.